2002
DOI: 10.2320/matertrans.43.2177
|View full text |Cite
|
Sign up to set email alerts
|

TEM Observation of Interfaces between Particles in Al-Mg Alloy Powder Compacts Prepared by Pulse Electric Current Sintering

Abstract: Aluminum-Magnesium (Al-Mg) alloys powders with various amounts of Mg addition were sintered using the pulse electric current sintering (PECS) process. The behavior of Mg in the surface oxide film and the effect of Mg amounts on characters of the interfaces between Al-Mg alloys powder particles were investigated using transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS). The results showed that there were interfaces of direct metal/metal bonding and metal/oxide layer/metal bondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…compositions of the crystalline particles depended on the amount of Mg addition in the alloys and sintering temperature, which are determined to be MgAl 2 O 4 or MgO, or both of them. Recently, we have reported the results at a sintering temperature of about 0.72 times as the solidus temperature for Al-Mg alloys 19) and those of Al-1.0 mass%Mg alloy at various sintering temperature. 20) Using the same analyses method, we have investigated the compositions of the crystalline particles on each Mg content and various sintering temperatures.…”
Section: Microstructure Of the Fractured Surfacementioning
confidence: 94%
“…compositions of the crystalline particles depended on the amount of Mg addition in the alloys and sintering temperature, which are determined to be MgAl 2 O 4 or MgO, or both of them. Recently, we have reported the results at a sintering temperature of about 0.72 times as the solidus temperature for Al-Mg alloys 19) and those of Al-1.0 mass%Mg alloy at various sintering temperature. 20) Using the same analyses method, we have investigated the compositions of the crystalline particles on each Mg content and various sintering temperatures.…”
Section: Microstructure Of the Fractured Surfacementioning
confidence: 94%
“…They concluded, in agreement with further researches, 16,17 that the zigzag line in the stir zone did not affect mechanical properties of the weld. Different studies, [17][18][19] conducted from the chemical point of view, reported that the amorphous Al 2 O 3 oxide in Al-Mg alloys easily changes into crystalline AlMg 2 O 4 or MgO phases during long time heating such as sintering and diffusion bonding. Therefore, there is a possibility that thermal cycle of FSW changes surface oxide layer from amorphous Al 2 O 3 to the crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the tendency of change on the real density was consistent with the change of the apparent relative density. 25) It indicates that the observation of the linear shrinkage is very useful to understand the densification behavior of the powder compacts during the SPS process. Table 1 gives the measured relative density of the samples sintered by the SPS process at various sintering temperatures with a loading pressure of 600 MPa and a holding time of 10 min.…”
Section: Densification Behavior During the Sps Processmentioning
confidence: 99%